Spirit of the game: the excitement of getting together on INFORMS sports day / Suhaida Halamy, Dr Hajah Imilia Ibrahim and Muhammad Amierul Haqeem Mohd Faizan - Halamy, Suhaida; Ibrahim, Imilia; Mohd Faizan, Muhammad Amierul Haqeem (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Each semester, INFORMS, as the student association, gears up to infuse excitement into student life with various activities. They aimed to engage students in physical activities and foster a spirit of well-being. INFORMS Sports Day was held on Saturday, 2nd December 2023, at UiTM Sports Complex, Samarahan Campus. The event featured exciting sports competitions like Futsal and Netball, allowing students to showcase their athletic prowess and teamwork. Organizing such activities can inspire students to embrace an active and healthy lifestyle. The planning for the INFORMS Sports Day began early in the semester. The committee, alongside advisor Dr. Hjh Imilia Ibrahim, dedicated significant effort to guaranteeing the smooth execution of the program. Each committee member was assigned specific tasks to oversee throughout the entire program. This division of responsibilities was essential for maintaining order and efficiency, ensuring that INFORMS Sports Day would be a well-organized and enjoyable experience for everyone involved.